Pengaruh Indeks Massa Tubuh (IMT) dan Kadar Kolesterol dengan Hipertensi di Puskesmas Gerung Kabupaten Lombok Barat Nusa Tenggara Barat - Putu Ardhyana Yogeswara; Ety Retno Setyowati; Siti Ruqayyah; Deny Sutrisna Wiatma (Jurnal Ners, 2023)
Hypertension is a health problem that often occurs throughout the world. Over time, the prevalence of hypertension has increased every year. Hypertension can be caused by an increase in Body Mass Index (BMI) and total cholesterol levels. Many studies state that there is a relationship between body mass index and cholesterol levels with hypertension. However, there are also studies with different results which state that there is no relationship between body mass index and total cholesterol levels with hypertension. To determine whether there is a relationship between body mass index and total cholesterol levels with hypertension at the Gerung Community Health Center, West Lombok Regency, West Nusa Tenggara. This study used an observational analytic study with a cross-sectional study design, with a sample of 30 respondents who met the inclusion criteria, namely patients with hypertension, hypercholesterolemia and obesity who were treated at the Gerung Health Center in West Lombok Regency, West Nusa Tenggara and patients who were willing be a research sample. There is a significant relationship between body mass index (BMI) and hypertension at the Gerung Health Center in West Lombok Regency, West Nusa Tenggara with a p-value of 0,000 (p-value <0,05) and a correlation value of 0,671. There is a significant relationship between total cholesterol levels and hypertension at the Gerung Health Center in West Lombok Regency, West Nusa Tenggara with a p-value of 0,001 (p-value <0,05) and a correlation value of 0,599. There is a significant relationship between body mass index (BMI) and total cholesterol levels with hypertension at the Gerung Community Health Center, West Lombok Regency, West Nusa Tenggara.